Horn plates in the management of supracondylar femoral fracture in dogs: An experimental study - Aithal, H P; Singh, G R; Amarpal, Amarpal (The Indian Journal of Animal Sciences, 2012)
In the present study, plates prepared from buffalo horn were evaluated for the fixation of supracondylar femoral fracture in experimental dogs. The results were compared with standard stainless steel plated animals, using different intraoperative and postoperative clinical observations, evaluation of stifle joint function and radiological examinations of the fracture site as parameters for evaluation. Horn plates were technically easier to apply than stainless steel plates. The duration of surgery and the extent of soft tissue manipulation was comparable between the groups. Postoperative inflammation and oedema were relatively more with horn plates. Weight bearing and range of joint motion improved progressively to attain near normal level at the end of observation, i.e. 90 days, in stainless steel plated animals. Recovery in joint motion and weight bearing was delayed in horn plated animals. Fixation failure was seen in 2 (40%) stainless steel plated animals, whereas rigid fixation was maintained with horn plates in all the animals till the end of observation. Fracture healing was comparable among the groups.